A Comparative Analysis of Environmental and Social Practices in the Sugar Industries of Brazil and Southern Maharashtra, India - , Y. P. Desai, D. M. Bongarde, S. P. Khandekar, P. D. Patil (Archives of Current Research International, 2024)
This paper reviews the worldwide sugar business, focusing on South Maharashtra in India and Brazil. The study employs a systematic approach to evaluate the environmental sustainability, as well as the social and economic impact of sugar production in these regions. Businesses are reassessing their tactics as people become more aware of social fairness and climate change, making the sugar industry an ideal subject for research due to its important environmental and social ramifications. While Brazil's sugar market has grown dramatically due to advances in farming methods and technologies, Southern Maharashtra continues to rely significantly on traditional agricultural practices, particularly sugar cultivation. The intent is to shed light on the contrasts between these industries by analyzing their environmental assessment methodologies, social responsibility efforts, and sustainable business practices. Furthermore, it attempts to add useful insights to the continuing discourse about promoting sustainable practices in the global sugar industry. The sugar industry has a lot of potential for growth due to its byproducts such as ethanol, biogas, and different agro-based products which further bolster the environmental sustainability potential.